The Fall of Oil Prices and Changes in the Dynamic Relationship between the Stock Markets of Russia and Kazakhstan - Sultonov, Mirzosaid (Journal of Reviews on Global Economics, 2015)
In this paper, we investigate the dynamic relationship between the stock markets of Russia and Kazakhstan and the effect of oil price volatility on both markets. This research differs from the studies of the effect of oil prices on stock markets as it considers the relationship between two post-Soviet transition and developing economies that are highly dependent on the export of oil. The derived results reveal significant interdependence among variations in the stock markets of Russia and Kazakhstan, crude oil prices and the association of falling oil prices with global and Russian crises.